Atividade antinociceptiva e antioxidante do fitol em modelos in vivo e in vitro - Santos, Camila Carolina de Menezes Patrício (2011)
This study was conducted in order to draw a profile of pharmacological activity of phytol, a alcohol diterpene. The study was conducted in three steps: (1) evaluation of acute toxicity, (2) evaluation the activity of phytol on the CNS, focusing on the analgesic activity, and (3) evaluation of antioxidant activity. In the first two stages, the study was conducted in vivo and in third, the study was in vitro. The results were expressed as mean ± standard error of mean (S.E.M.), were considered significant when p <0.05. In the first step, the phytol showed low toxicity, causing no changes in biochemical and hematological parameters of the animals, have been determined the LD50 in 1153.39 (944.56 1.408.40) mg/kg. In the following tests, the phytol was administered intraperitoneally (i.p.) at doses of 25, 50, 100 and 200 mg/kg. The phytol showed profile of depressant drugs CNS, without compromising the motor coordination of animals. The antinociceptive activity of phytol was investigated by chemical models (test of abdominal contortions induced by acetic acid and formalin test) and thermal (hot plate test) of nociception in mice. In all tests, the phytol showed a highly significant antinociceptive effect at both the central and peripheral. However, the effect of phytol was not reversed by the antagonists naloxona (opioid system) and glibenclamida (K +ATP channels), demonstrating that at least directly, the phytol does not act by these mechanisms. In the antioxidant activity in vitro of phytol through three methodologies, one for evaluating the effect of phytol on lipid peroxidation in the TBARS test, and other two to investigate if the phytol acted as substance scavenging of free radicals to hydroxyl radical (OH) and nitric oxide (NO). In all tests, the phytol showed strong antioxidant activity, which can be attributed to their structural feature, since phytol is a unsaturated alcohol of branched-chain, and antioxidant properties may be related to the hydroxyl group (OH) present in its molecule. Probably the phytol, by reacting with a free radical, donates hydrogen atoms with an unpaired electron (H.), converting free radicals into less reactive species. Since several evidences show the involvement of these reactive species inthe mechanism of pain, the antioxidant activity of phytol may be contributing to its antinociceptive effect.